Analisis Hukum Atas Penerapan Klasifikasi Saham Dengan Hak Suara Multipel Di Pasar Modal Indonesia - Andy Rahmad Wijaya (Fakultas Hukum, Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
The Financial Services Authority (OJK) issued OJK Regulation Number 22/POJK.04/2021 concerning the Application of Stock Classification with Multiple Voting Rights by Issuers with Innovation and High Growth Rates conducting Public Offerings of Equity Securities in the form of Shares (POJK 22/2021). The problem raised in this research is the implications for investors on the regulation of the implementation of stock classification with multiple voting rights by issuers in the capital market. This research is a normative or doctrinal legal research, which describes, explains, and analyzes the optional policies carried out by OJK through POJK 22/202. The analysis is carried out using a qualitative descriptive approach that begins with collecting legal materials, qualifying them, connecting theories related to research problems, drawing conclusions to determine results and recommendations. The results of this study indicate that issuers who exercise multiple voting rights in the capital market can make the majority shareholder unable to control the company. Investors who will own shares in issuers that implement this policy only have the advantage of enjoying dividends only if the issuer makes a profit. However, if the issuer suffers a loss, the investor will suffer the biggest loss.